Mathematical formulations for complex resource scheduling problems - Lalita, T. R. (Hyderabad: Indian Statistical Institute, 2021)
This thesis deals with development of effective models for large scale real-world resource scheduling problems. Efficient utilization of resources is crucial for any organization or industry as resources are often scarce. Scheduling them in an optimal way can not only take care of the scarcity but has potential economic benefits. Optimal utilization of resources reduces costs and thereby provides a competitive edge in the business world. Resources can be of different types such as human (personnel-skilled and unskilled), financial(budgets), materials, infrastructures(airports and seaports with designed facilities, windmills, warehouses$1 (Barea, hotel rooms etc) and equipment (microprocessors, cranes, machinery, aircraft simulators for training), etc. Typically, scheduling of resources is done over a period of time (planning horizon), but in many cases there are other dimensions to the problem induced by limited resources.s
The Integrated Staff And Task Scheduling Problem -- Planning Airport Check-in Counter Allocation -- Berth Assignment and Crane Scheduling at Ports -- Extension of Resource Scheduling Models to Wind Power Scheduling
Thesis (Ph.D.)- Indian Statistical Institute, 2021
Includes bibliography
Guided by Prof. G S R Murthy
Keywords: Resource Scheduling; Wind Power Scheduling; Crane Scheduling; Project Management; Simulation; Network Model